Dislocation behavior in Cu single crystal joints under the ultrasonically excited high-strain-rate deformation. (1st April 2023) - Ma, Qiuchen; Ma, Jingyuan; Zhou, Jianli; Zheng, Xiaoxiong; Ji, Hongjun
Highlights: The interfacial evolution for ultrasonically welded joints was used to clarify the coupling effects of ultrasonic excitation and high-strain-rate deformation. Transmission Kikuchi diffraction and transmission electron microscopy were used to analyze grain orientation and deformed microstructures simultaneously. Ultrasonic excitation dramatically weakened the constraint of high-strain-rate and characteristic orientations on dislocation motion. The first-principle calculation and applied strain-rate analysis were conducted to discuss the preferred deformation mechanism to accommodate the imposed plastic strain. Abstract: The coupling effects of ultrasonic excitation and high-strain-rate deformation are the core factors for weld formation during ultrasonic welding. However, interfacial deformation behavior still shrouds in uncertainty because of the contradictory features between mutual dislocation retardation caused by severely frictional deformation and ultrasonic-accelerated dislocation motion. [101] and [111]-oriented Cu single crystals which tended to form geometrically necessary boundaries (GNBs) were selected as the welding substrates to trace the uniquely acoustoplastic effects in the interfacial region under the ultrasonically excited high-strain-rate deformation. It was indicated that for a low energy input, micro-welds localized at the specific interface region, and equiaxed dislocation cells substituting for GNBs dominated in the initial single crystal rotation region. As the welding energy increased, continuous shear deformation drove the dynamic recrystallization region covered by equiaxed grains to spread progressively. Limited discrete dislocations inside the recrystallized grains and nascent dislocation cells at the grain boundaries were observed in [101] and [111] joints simultaneously, suggesting that the ultrasonic excitation promoted motion of intragranular dislocation and pile-up along the sub-grain boundaries. The interfacial morphology before and after expansion of recrystallization region all exhibited the weakening of orientation constraint on dislocation motion, which was also confirmed by the similar micro-hardness in joint interface. The first-principle calculation and applied strain-rate analysis further revealed that ultrasonic excitation enhanced dislocation slipping, and enabled dislocation motion to accommodate severe plastic deformation at a high-strain-rate.